2014
DOI: 10.1097/scs.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Rhabdomyosarcoma in Adults

Abstract: Head and neck RMS in adults is a rare malignancy with a poor outcome, which is more likely to have CLN involvement compared with other soft tissue sarcomas of the head and neck. Standard treatment for AHNRMS should comprise surgery and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 15 publications
4
38
4
Order By: Relevance
“…The clinical presentation of HNRMS is divided into 3 sub-sites based on its anatomic location and local relapse: parameningeal (PM), including the paranasal sinuses, nasopharynx, nasal cavity, middle ear, mastoid, parapharyngeal region, pterygopalatine and infratemporal fossa; orbital; and non-PM / non-orbital site, encompassing the neck, face, oral cavity, cheek, external ear, scalp and larynx [7]. PM subsite is the most common presentation and is associated with the least favorable outcome compared to other locations [4-6, 8]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical presentation of HNRMS is divided into 3 sub-sites based on its anatomic location and local relapse: parameningeal (PM), including the paranasal sinuses, nasopharynx, nasal cavity, middle ear, mastoid, parapharyngeal region, pterygopalatine and infratemporal fossa; orbital; and non-PM / non-orbital site, encompassing the neck, face, oral cavity, cheek, external ear, scalp and larynx [7]. PM subsite is the most common presentation and is associated with the least favorable outcome compared to other locations [4-6, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…ERMS is the most common variant, being associated with the most favorable outcome compared to other variants [6, 8]. ERMS occurs in younger patients and shows a morphologic resemblance to fetal skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is certainly impossible to fully comprehend the complexities of individual treatment decisions when looking at patients in aggregate. However, given that 46 % of our elderly cohort were deemed healthy enough to receive local therapy (surgery and/or radiation), as well as the substantial potential for improved survival given the poor prognosis of undertreated RMS, and the fact that multiple studies have shown chemotherapy to be a mainstay of treatment for RMS, it is likely that chemotherapy is under-utilized in the EP group [5,[9][10][11]. This is also particularly disturbing when >71 % of YPs received chemotherapy.…”
Section: Discussionmentioning
confidence: 88%